Long-term Kentucky bluegrass cultivation enhances soil quality and microbial communities on the Qinghai-Tibet Plateau - Li, Sida; Shi, Zhenghai; Liu, Wen-hui; Li, Wen; Liang, Guoling; Liu, Kaiqiang (Frontiers in Plant Science, 2025)
IntroductionNature-based Solutions (NbS) provide a comprehensive strategy for environmental management, focusing on the protection, sustainable use, and restoration of natural and modified ecosystems. Cultivated grasslands are a form of NbS, offering benefits such as increased biodiversity, improved soil fertility, and greater ecosystem resilience. They are widely acknowledged for their positive impact on restoring degraded grasslands. Kentucky bluegrass (Poa pratensis L.) is widely used for restoring degraded grasslands on the Qinghai-Tibet Plateau. However, long-term cultivation of Kentucky bluegrass can lead to above-ground degradation, which challenges its effectiveness in restoring ecosystem health.MethodsThis study investigates the impacts of Kentucky bluegrass cultivation on soil quality, focusing on soil nutrients, enzyme activities, and microbial communities across different recovery stages. Field experiments were conducted to analyze soil quality dynamics during early (2nd year), mid (6th year), and late (10th year) succession stages of cultivated grasslands on the Qinghai-Tibet Plateau. Our results show that in the early and mid-stages, soil total nitrogen, total phosphorus, and organic carbon storage were significantly lower compared to undegraded grasslands, with the lowest soil quality observed in the early stage (P< 0.05). However, by the late stage, soil quality significantly improved, with total nitrogen, total phosphorus, and organic carbon contents exceeding those of undegraded grasslands by 14.59%. These improvements were driven by enhanced microbial community dynamics and increased nitrogen and carbon cycling enzyme activities, which promoted nutrient utilization and organic matter decomposition. This process was accompanied by a rise in microbial diversity, supporting soil resilience and ecosystem function. Soil total nitrogen emerged as a key determinant of soil quality in both natural and cultivated grasslands, and appropriate nitrogen fertilization strategies were found to effectively enhance grassland productivity and ecosystem health.DiscussionOverall, this study highlights the potential of Kentucky bluegrass in restoring degraded grasslands by improving soil fertility and microbial community structure over time, providing insights into sustainable management practices to maintain soil fertility and ecosystem services on the Qinghai-Tibet Plateau.